Genomic insights into clinical non-O1/non-O139 Vibrio cholerae isolates in Japan - Yohei Kobayashi; Masato Suzuki; Shuntaro Umeda; Keisuke Oka; Kenichi Takahashi; Keigo Shibayama; Shinichiro Shibata (Microbiology Spectrum)
ABSTRACT Non-O1/non-O139 Vibrio cholerae (NOVC) causes sporadic intestinal infections and systemic symptoms. Recently, global warming has led to an increase in NOVC infections; however, there have been no reports on the genomic analysis of clinical NOVC isolates in Japan, and the molecular understanding of NOVC remains inadequate. We identified three cases of NOVC infection in Nagoya, Japan, in 2020 and performed genomic analysis to reveal the molecular characteristics of these isolates and compared them with those of previously reported clinical cases. Phylogenetic analysis revealed high diversity. This result indicates that the three cases were sporadic within the area over a short period of time from multiple contaminated sources. However, most clinical isolates carried virulence factor genes encoding El Tor type hemolysin, type VI secretion system (T6SS), and repeats-in-toxin toxin, and approximately half of the isolates carried nanH encoded on VPI-2, as well as the type III secretion system (T3SS). Additionally, detailed whole-genome sequencing (WGS) analysis revealed various types of T3SS, T6SS, VPI-2, and VSP-2. Variations in the number of Rep1 units of VopM were observed in the T3SS of the NOVC isolates in this study. The T6SS type identified in this study consisted of a large cluster and auxiliary clusters, showing diversity among the NOVC isolates. We recommend continued monitoring of clinical NOVC isolates as horizontal transmission along with host and environmental recombination may lead to changes in virulence.IMPORTANCEAlthough reports of non-O1/non-O139 Vibrio cholerae (NOVC) infections are rare, their actual incidence remains uncertain. This is partly due to nonspecific symptoms, the absence of a surveillance system in most countries including Japan, and the lack of appropriate laboratory culture techniques. However, NOVCs in the environment are increasing due to global warming, and the risk of NOVC infections is increasing. In this study, we conducted a comprehensive genomic analysis of clinical NOVC isolates from a city in Japan and compared their virulence factor profiles with those of previously reported clinical isolates using whole-genome sequencing (WGS). This result indicates that some sporadic cases have occurred in the area, suggesting that there are multiple sources of NOVC infection. The accumulation of such data will enhance our understanding of the pathogenicity of NOVCs and improve diagnostic accuracy.